Effects of Micron Fish Bone with Different Particle Size on the Properties of Silver Carp (Hypophthalmichthys molitrix) Surimi Gels - Tao Yin; Jae W. Park; Shanbai Xiong (Journal of Food Quality)
Qualities of silver carp surimi (SCS) gels incorporated with micron fish bone of different particle size (22 to 0.12 μm) were evaluated. Textural values, whiteness, and water holding capacity of the SCS gels with setting significantly increased (P<0.05) as the micron fish bone particle size decreased. As the particle size decreased, more calcium ion was apparently released from the fish bone (P<0.05). Consequently the released calcium ion increased the activity of endogenous transglutaminase (TGase) and resulted in the formation of more myosin heavy chain (MHC) cross-links in the SCS gel with setting. Fish bone with particle size below 0.48 μm was steadily trapped in the three-dimensional SCS gel network without disrupting the matrices. Results indicated that size reduction of the incorporated micron fish bone improved qualities of the SCS gel with setting by the means of releasing more calcium ion and maintaining better gel matrices.